UMP should seriously look into Artificial Intelligence development as future driver of tertiary education Chancellor - UMP, PNC (2019)
The Chancellor of Universiti Malaysia Pahang (UMP) and the country’s reigning King, His Majesty Seri Paduka Baginda The Yang di-Pertuan Agong Al-Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah Ibni Almarhum Sultan Haji Ahmad Shah Al-Musta’in Billah, has urged the university to place more emphasis on the development of Artificial Intelligence (AI) as one of the future drivers of tertiary education.